EVALUASI COATING MATERIALS UNTUK MELINDUNGI BAKTERI PROBIOTIK PSEUDOALTEROMONAS PISCICIDA SELAMA PROSES MIKROENKAPSULASI DAN PENYIMPANAN - DIAN EKA RAMADHANI; Lesmanawati (Universitas Djuanda, 2021)
Disease is an obstacle in Pacific white shrimp culture that can cause economic losses. Probiotic bacteria Pseudalteromonas piscicida 1Ub RfR is able to improve the growth performance and immune responses of Pacific white shrimp and has the potential to be developed into dry products to make it more practical for use in the field. This study aims to obtain the best coating materials that can protect probiotic bacteria during the microencapsulation and storage process. This research was conducted in September-December 2020 at the Laboratory of Microbiology of IPB Sukabumi Campus and South-East Asia Food and Agricultural Science and Technology (SEAFAST). This research consists of 2 Chapters, Chapter 1 to obtain the best coating materials and Chapter 2 to obtain the best results after the microencapsulation process. Coating materials used in this study were whey protein and maltodextrin. The microencapsulation technique used is freeze drying and spray drying. The probiotic bacteria used was P. piscicida from Fish Health and Management Laboratory, Department of Aquaculture, FPIK IPB and was marked with rifampicin resistance (1Ub RfR). The research in Chapter 1 consisted of 4 treatments, including K (without coating material), A (single coating with whey protein), B (single coating with maltodextrin), and C (double coating with whey protein and maltodextrin). Furthermore, each treatment in Chapter 1 is continued for the microencapsulation process. The results showed that the treatment with double coating and encapsulated by freeze drying was the best probiotic products compared other treatments.